Studies on Status and Host Range of Soft Rot Disease of Cabbage (Brassica oleracea var Capitata) Kashmir Valley - S. A. Mir2, M. Y. Zargar2 and P. A. Sheikh1, K.A. Bhat1*, N.A. Bhat2, S.D. Masoodi1 (Journal of Phytology, 2010)
Cabbage (Brassica oleracea var. capitata) is one of the most important vegetable crops grown in Kashmir throughout the year. The crop suffers considerably because of soft rot. Survey conducted during 2008-09 revealed that soft rot of cabbage is prevalent in all the vegetable markets of Kashmir Valley. The disease was considerably higher in two of the districts viz. Anantnag and Baramullah than Srinagar. The highest incidence was recorded in Anantnag. Upon isolation the causal pathogen responsible for soft rot in cabbage under temperate conditions of valley was identified as Erwinia carotovora sub-sp. carotovora. Studies on host range of the bacterium under artificial inoculation revealed that all the seven tested vegetable species, representative of the families, were susceptible to soft rot. Key words: Soft rot, Erwinia carotovora sub-sp. carotovora, Host range <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">K.A. Bhat et al. Studies on Status and Host Range of Soft Rot Disease of Cabbage (Brassica oleracea var Capitata) Kashmir Valley. J Phytol 2/10 (2010) 55-59